(untitled) (ELang | An English Language Education Journal, 2010)
This paper aims to find out the effectiveness of Students best photograph picture technique in teaching writing descriptive text by seeking the significant difference in students’ scores before and after treatment. The method used by the writer was quasi experimental design. The participants who were involved in the research were the students of SMPN 3 Cileunyi. The samples of this study were two classes: A and B. In collecting the data, the instruments are tests and questionnaire. The pre-test scores was analyzed to measure the students’ ability in writing descriptive text before receiving the treatment. The treatment was given only to the experimental group. The result of post-test was analyzed to find out the scores development after sample receives the treatment. The questionnaire was provided towards the experimental group to know their responses about students’ best photograph technique in teaching writing descriptive text. The t-test was used to compare the values of the means from two examples. With the df = N1 + N2 – 2 = 60 – 2 = 58, at p = .05 0f two tailed (level of significance), the critical value of t is 2.000. From the calculation, the ttest value is 2.173. The writer concluded that t-test is higher than t table (2.173 > 2.000). It means that the null hypothesis is rejected and the alternative hypothesis is accepted that says: There is significance difference between students’ best photograph technique and the conventional method in teaching writing descriptive text. The result also shows that this technique is effective. Seventy two percent (72%) of students felt comfortable, more easily, and increasing in writing descriptive with students’ best photograph technique in teaching writing descriptive text. This response strengths the effectiveness of students’ best photograph technique in teaching writing descriptive text. The finding of the research shows that students’ best photograph technique can be useful in improving students’ ability in writing descriptive text.